Classical and damage mechanics-based models for lead-free solder interconnects - Lai, Zheng Bo (2009)
Solder joint reliability (SJR) is the key concern in electronics packaging, primarily for ball grid array (BGA) packages. It affects the overall performance and reliability of electronics devices. In this project, the response of Sn-4.0Ag-0.5Cu (SAC405) lead-free solder joints in a typical BGA package is examined. Finite element (FE) analysis is employed along with published experimental data in establishing a thorough understanding of the mechanics and failure process of the solder joints. The accuracy of FE results for SJR is highly dependent on the solder constitutive behavior prescribed in the analysis. In the respect, unified inelastic strain theory (Anand model) is employed with model parameters extracted from series of published tensile tests data at different temperatures and strain rates. The model is refined further to ensure better predictive capability. The SJR of a BGA test package subjected to solder reflow process and temperature cycles is examined. The critical solder joint is identified at location near to the die corner. The highest stress and inelastic strain magnitudes are calculated at the component side of the solder/intermetallics compound (IMC) interface. Stress-strain hysteresis suggested that solder joint fatigue is primarily contributed by localized shear effect. Both strainand energy-based life prediction models have been developed for the accelerated reliability cycles. The failure process of solder/pad interface under applied monotonic loading is described. In this respect, the Cohesive Zone Model (CZM) is evaluated within the FE framework to simulate the relatively brittle interface. Materials parameters for CZM are established based on published data of solder ball shear tests. It was found that localized cracking of the solder/pad interface in lead-free solder joints under shear test setup is initiated by tensile stress field due to shear tool clearance.